Progesterone Receptor Membrane Component 1 as the Mediator of the Inhibitory Effect of Progestins on Cytokine-Induced Matrix Metalloproteinase 9 Activity In Vitro. (February 2014) - Allen, Terrence K.; Feng, Liping; Grotegut, Chad A.; Murtha, Amy P.
Progesterone (P4) and the progestin, 17α-hydroxyprogesterone caproate, are clinically used to prevent preterm births (PTBs); however, their mechanism of action remains unclear. Cytokine-induced matrix metalloproteinase 9 (MMP-9) activity plays a key role in preterm premature rupture of the membranes and PTB. We demonstrated that the primary chorion cells and the HTR8/SVneo cells (cytotrophoblast cell line) do not express the classical progesterone receptor (PGR) but instead a novel progesterone receptor, progesterone receptor membrane component 1 (PGRMC1), whose role remains unclear. Using HTR8/SVneo cells in culture, we further demonstrated that 6 hours pretreatment with medroxyprogesterone acetate (MPA) and dexamethasone (Dex) but not P4 or 17α-hydroxyprogesterone hexanoate significantly attenuated tumor necrosis factor α-induced MMP-9 activity after a 24-hour incubation period. The inhibitory effect of MPA, but not Dex, was attenuated when PGRMC1 expression was successfully reduced by PGRMC1 small interfering RNA. Our findings highlight a possible novel role of PGRMC1 in mediating the effects of MPA and in modulating cytokine-induced MMP-9 activity in cytotrophoblast cells in vitro.